2012
DOI: 10.1021/ja3003217
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity in Potassium-Doped Few-Layer Graphene

Abstract: Here we report the successful synthesis of superconducting potassium-doped few-layer graphene (K-doped FLG) with a transition temperature of 4.5 K, which is 1 order of magnitude higher than that observed in the bulk potassium graphite intercalation compound (GIC) KC(8) (T(c) = 0.39 K). The realization of superconductivity in K-doped FLG shows the potential for the development of new superconducting electronic devices using two-dimensional (2D) graphene as a basis material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(87 citation statements)
references
References 36 publications
1
86
0
Order By: Relevance
“…Although we have only examined how these metallic impurities can impact the electrochemical responses of RGOs, it is important to keep in mind that other properties can be affected as well. For metallic elements with higher levels of contamination, potassium doping is known to have profound effects on the electronic properties of graphene (53,54), whereas the presence of aluminum on graphene greatly increases its affinity for gases, such as N 2 O and CO (55,56). Additionally, graphene films have been envisaged to function as water desalination systems because of the potential of tuning pore sizes to allow permeation or rejection of different ions (57).…”
Section: Resultsmentioning
confidence: 99%
“…Although we have only examined how these metallic impurities can impact the electrochemical responses of RGOs, it is important to keep in mind that other properties can be affected as well. For metallic elements with higher levels of contamination, potassium doping is known to have profound effects on the electronic properties of graphene (53,54), whereas the presence of aluminum on graphene greatly increases its affinity for gases, such as N 2 O and CO (55,56). Additionally, graphene films have been envisaged to function as water desalination systems because of the potential of tuning pore sizes to allow permeation or rejection of different ions (57).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the prediction has been verified experimentally for Ca-intercalated graphene on either the Si or the C face of a SiC substrate, finding T c = 7 K [9]. Experimentally, it also has been observed that KC 8 graphite [10] and K-intercalated few layer graphene on SiC are superconducting [11], where theoretical arguments for superconductivity in the latter material have been presented in Ref. [12].…”
Section: Introductionmentioning
confidence: 85%
“…4,5) The decoration or intercalation of alkali metal increases the DOS around E F via electron doping and gives rise to an additional interlayer band and vibrational modes, which enhance the electron-phonon coupling. The resulting superconducting transition temperature (T c ) reach ∼8.1 K. [4][5][6][7][8][9][10][11] The candidate materials for 2D superconductors are not limited to graphene-based materials. For example, silicenethe Si cousin of graphene -is also predicted to behave as a BCS-type superconductor after electronic doping.…”
Section: 3)mentioning
confidence: 99%